Stent-Assisted Coiling of Wide-Neck Intracranial Aneurysms Using Low-Profile LEO Baby Stents: Initial and Midterm Results - Aydin, K.; Arat, A.; Sencer, S.; Barburoglu, M.; Men, S. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Low-profile self-expandable stents were recently introduced for the treatment of wide-neck intracranial aneurysms. This study investigated the initial and midterm clinical and angiographic results of LEO Baby stent–assisted coiling in the treatment of wide-neck intracranial aneurysms.MATERIALS AND METHODS: A retrospective review was performed to identify patients who were treated with LEO Baby stent–assisted coiling. Eighty patients with 80 wide-neck intracranial aneurysms were included in the study. Eleven patients (13.8%) presented with subarachnoid hemorrhage. All patients were treated with LEO Baby stent–assisted coiling. Technical success and immediate postprocedural clinical and angiographic outcomes were evaluated. Seventy-three patients attended angiographic and clinical follow-up for a mean duration of 7.2 ± 3.8 months. Periprocedural and delayed complications were reviewed. Preprocedural and follow-up clinical statuses were assessed by using the modified Rankin Scale.RESULTS: The technical success rate of the procedure was 97.5%. The immediate postprocedural angiography revealed a complete occlusion of the aneurysm in 75% of the 80 patients. The last follow-up angiograms showed complete occlusion in 85.7% of the 77 patients with an angiographic follow-up. Of the 77 patients with a follow-up angiography, 6.5% showed an increase in the filling status of the aneurysm and 5.2% required retreatment. The overall procedure-related complication rate, including asymptomatic complications, was 11.3%. The permanent morbidity rate was 3.8%. There was no mortality in this study.CONCLUSIONS: This case series demonstrates the relative safety, efficacy, and midterm durability of the LEO Baby stent–assisted coiling procedure for the treatment of wide-neck intracranial aneurysms.AcomAanterior communicating arterySACstent-assisted coiling